The Value Relevance of IFRS Adoption in Indonesia - Juniarti Juniarti; Ferbiana Helena; Karina Novitasari; Wenny Tjamdinata (Institute of Research and Community Outreach - Petra Christian University, 2018)
Pros and cons of the benefits of IFRS adoption have become an ongoing debate following the inconclusive results of prior studies. Whether IFRS increase value relevance of accounting information or not, especially in developing countries is an interesting and relevance research question. Indonesia as one of the developing countries that committed to adopting IFRS has an interest in obtaining empiric evidence on the value relevance of accounting information after nearly five years of IFRS implementation. This study aims to fill the need to enhance adopters' compliance with the standard. Ohlson Modified Model (1995) is used to test the value relevance of accounting information. Using longitudinal data of listed manufacturing companies in Indonesia Stock Exchange (IDX), this study confirms that value relevance of accounting information increase after IFRS adoption than before adoption. The results robust using Pooled Least Square and Random effect model.